PENGARUH SISTEM PEMBELAJARAN, SISTEM INFORMASI, MUTU PELAYANAN, DAN FASILITAS KAMPUS TERHADAP TINGKAT KEPUASAN MAHASISWA STIE SBI YOGYAKARTA SELAMA MASA PANDEMI COVID-19 - Surawan, Surawan; Aji Hutama, Bayu Waskita (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
This study aim for determine and analyze the effect of learning system, information system, service quality, and campus facilities to satisfaction students level of STIE SBI Yogyakarta during the COVID19 pandemic period. This Study use quantitative method with technique data analize using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test , f test , and coefficient determinations test by using SPSS 21.0 application for windows . Population on this study is active Student of the Indonesian Business Solutions School of Economics, Yogyakarta teaching year 2022/2023 as many as 623 people. Technique of sample taking by proportional random sampling method with slovin formula amount as many as 86 people. Data collection technique using questionnaire. Results of this study indicate that : (1) learning system influential positive And significant to satisfaction student; (2) information system influential positive And significant to satisfaction student; (3) service quality influential positive And significant to satisfaction student; (4) campus facilities influential positive And significant to satisfaction student. Learning system, information system, service quality, and campus facilities own influence positive And significant in a manner together to satisfaction students level of STIE SBI Yogyakarta during the COVID19 pandemic.. Keywords : Learning System, Information System, Service Quality, Campus Facilities, Student Satisfaction.